Cytotoxicity and genotoxicity evaluation of antidote oxime HI-6 tested on eight cell lines of human and rodent origin - Svobodova, Hana; Jost, Petr; Stetina, Rudolf (General physiology and biophysics, 2012)
Oxime HI-6 is an efficient reactivator of the acetylcholinesterase inhibited by organophosphorous nerve agents. In this study we have estimated cytotoxicity of HI-6 by the colony forming assay and genotoxicity by the comet assay on human and rodent cell lines. IC50 of HI-6 assessed by the colony forming capacity was 3.59 mM for HeLa cells and 5.18 mM for a mouse cell line L929. Small difference in cytotoxicity was found among other cell lines tested: IC50 was 1.61 mM for human A549 cells, 1.14 mM for UROtse line, 1.96 mM and 1.71 mM for Chinese hamster cells AA8 and UV-20, respectively. The A549 cell viability measured with the MTT test was 5 times decreased comparing 2 and 24 hours of HI-6 oxime treatment. The 5 mM HI-6 concentration reduced the viability within 2 hours to 95% only, however, it induced a significant number of DNA breaks in mouse cells L929, and also in human UROtse and HepG2 cells. 1-β-D-arabinofuranosylcytosine (10(-4) M) and hydroxyurea (10(-2) M), supplemented to the cultivation medium, did not cause any significant accumulation of DNA breaks during treatment, which indicated that the nucleotide excision repair was not acting on the induced DNA damage.
Keywords: mutageny; Cell Line; pyridinové sloučeniny; DNA Damage; Rats; křečci praví; Cholinesterase Reactivators; poškození DNA; Cytotoxins; Mice; Oximes; Mutagens; krysa rodu Rattus; Pyridinium Compounds; antidota; zvířata; Humans; Lethal Dose 50; viabilita buněk; Cell Survival; Species Specificity; analýza kolonii tvořících jednotek; myši; Cricetinae; buněčné linie; Antidotes; druhová specificita; Colony-Forming Units Assay; LD50; oximy; reaktivátory cholinesterasy; cytotoxiny; lidé; Animals